Pyoderma gangrenosum and ulcerative colitis. Issue 3 (March 1980) - Thornton, J R; Teague, R H; Low-Beer, T S; Read, A E
Abstract : The relationship of pyoderma gangrenosum and ulcerative colitis remains uncertain. We investigating 14 patients with pyoderma gangrenosum by colonoscopy with multiple biopsies. Six patients had ulcerative colitis and all of these had disease affecting the whole colon. There were no correlations between exacerbations of the colitis and the onset or course of pyoderma gangrenosum. The remaining eight patients with pyoderma gangrenosum had no other disease and they were found to be significantly older than those patients with coexisting colitis (P less than 0.002).